Empathy for Pain: Insula Inactivation and Systemic Treatment With Midazolam Reverses the Hyperalgesia Induced by Cohabitation With a Pair in Chronic Pain Condition - Zaniboni, Caroline R.; Pelarin, Vinícius; Baptista-de-Souza, Daniela; Canto-de-Souza, Azair (Frontiers in Behavioral Neuroscience, 2018)
Empathy for pain is the ability to perceive and understand the pain in the other individual. Recent studies suggested that rodents have this social ability. GABAergic system has receptors in the brain structures involved in emotional processes as well as in the insular cortex. This area has been described as an important key in modulation of pain and empathy. The present study has investigated the role of insula and its Benzodiazepine-GABAA system on social modulation of pain induced by cohabiting with a mouse submitted to a neuropathic pain model. The insular cortex function was assessed by the structure inactivation (Exp. 1 and 2); the role of GABA system was evaluated by systemic treatment of midazolam (MDZ) (Exp. 3); and the role of GABAA receptors of insula were studied by bilateral MDZ microinjections in the structure (Exp. 4). Male Swiss mice were housed in groups or dyads. On dyads, after 14 days of cohabitation they were divided into two groups: cagemate nerve constriction and cagemate sham. After 14 days of familiarity, cagemates were evaluated on the writhing test. For group-housed, insula inactivation did not change nociception. For dyad-housed, cohabiting with a mouse in chronic pain increased the nociceptive response and the insula inactivation has reverted this response. Systemic MDZ attenuated nociception and intra-insula MDZ did not alter it. Our results suggest that cohabitation with a pair in chronic pain induces hypernociception, insula possibly modulates this response and the GABA system is also possibly involved, but not its insular mechanisms.